Extension of the B3LYP-dispersion-correcting potential approach to the accurate treatment of both inter-and intra-molecular interactions (2013)
We recently demonstrated that dispersion-correcting potentials (DCPs), which are atom-centered Gaussian-type functions that were developed for use with B3LYP (Torres and DiLabio in J Phys Chem Lett 3:1738-1744, 2012), greatly improved the ability of the underlying functional to predict non-covalent interactions. However, the recent application of the B3LYP-DCP approach to study the β-scission of the cumyloxyl radical led to a calculated barrier height that was over-estimated by ca. 8 kcal/mol. We demonstrate in the present work that the source of this error arises from the previously developed carbon atom DCPs, which erroneously alters the electron density in the C-C covalent-bonding region. In this work, we developed a new C-DCP with a form that was expected to less strongly influence the electron density in the covalent bonding region. Tests of the new C-DCP, in conjunction with previously published H-, N-, and O-DCPs, with B3LYP-DCP/6-31?G(2d,2p) on the S66, S22B, HSG-A, and HC12 databases of non-covalently interacting dimers showed that it is one of the most accurate methods available for treating intermolecular interactions, giving mean absolute errors (MAEs) of 0.19, 0.27, 0.16, and 0.18 kcal/mol, respectively. Additional testing on the S12L database of very large complexation systems gave an MAE of 2.6 kcal/mol, demonstrating that the B3LYP-DCP/6-31?G(2d,2p) approach to be one of the best-performing and most feasible methods for treating large systems containing significant non-covalent interactions. Finally, we showed that the modeling of C-C-making/C-C-breaking chemistry is well predicted using the newly developed DCPs. In addition to predicting a barrier height for the β-scission of the cumyloxyl radical, that is, within 1.7 kcal/mol of the high-level value, application of B3LYP-DCP/6-31+G(2d,2p) to 10 databases that include reaction barrier heights and energies, isomerization energies, and relative conformation energies gives performance that is among the best of all available dispersion-corrected density-functional theory approaches. © Springer-Verlag Berlin Heidelberg 2013.